IMPLEMENTASI MODEL PEMBELAJARAN THINK TALK WRITE BERBANTUAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA KELAS V SDN 56/I DESA ARO - Audianti, Ella; Sofwan, Muhammad; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low narrative writing skills of fifth-grade students at SDN 56/I Aro Village. Students experienced difficulty developing ideas, constructing a storyline, and writing coherently. This study aimed to improve narrative writing skills through the Think Talk Write learning model, supported by a series of pictures. The study used the Classroom Action Research (CAR) method, implemented in two cycles, each encompassing planning, implementation, observation, and reflection. Sixteen students participated in the study. Data were collected through observation, tests, and documentation, and then analyzed descriptively. The results showed an improvement in students' writing skills in each cycle. In the pre-action phase, the average student achievement was 30%. After the implementation of the action in Cycle I, the results increased to 43% in the first meeting and 56% in the second meeting. In Cycle II, the results increased again to 65% in the first meeting and reached 85% in the second meeting, categorized as good. This improvement occurred because the Think Talk Write model encouraged students to think, discuss, and write systematically, while the series of pictures helped students understand the sequence of events and develop story ideas. Based on these results, it can be concluded that the Think Talk Write learning model assisted by a series of picture media is effective in improving the narrative writing skills of fifth grade elementary school students.